Skip-beat! 01 - Nakamura, Yoshiki (Shojo beat manga., 2006)
Kyoko followed her true love, Sho, to Tokyo and supported him while he made it big as an idol. Now, he says she means nothing to him, so Kyoko sets out to become even bigger than Sho, but finds that her bitter heart may be her undoing.